The Influence Of Islamic Corporate Social Responsibility, Intellectual Capital, And Independent Commissioners On Financial Performance Moderated By Risk Management - Siti Salamah; Dirvi Surya Abbas (UNIVED Press, 2025)
Financial performance plays an important role in a company, and good financial services can have a positive effect on the company. The purpose of this study is to investigate and demonstrate the influence of Islamic Corporate Social Responsibility (ICSR), intellectual capital, and independent commissioners on financial performance, with risk management as a moderating variable. The research population consists of companies listed on the Jakarta Islamic Index 70 (JII 70) during the period 2020–2023, with a sample of 17 companies selected using purposive sampling. Data were analysed using Moderated Regression Analysis (MRA). The results indicate that ICSR has a negative impact on financial performance, intellectual capital has a significant positive impact, while liquidity has a significant negative impact on financial performance. Risk management can moderate the effect of ICSR on financial performance. Risk management cannot moderate the effect of IC on financial performance, but it can moderate the effect of independent commissioners on financial performance. This study can complement existing theories and research findings, provide references for improving and enhancing company performance, and assess benefits.